Regulation of gene expression by miR-144/451 during mouse erythropoiesis - Xu, Peng (Blood, 2019)
The microRNA (miRNA) locus miR-144/451 is abundantly expressed in erythrocyte precursors, facilitating their terminal maturation and protecting against oxidant stress. However, the full repertoire of erythroid miR-144/451 target messenger RNAs (mRNAs) and associated cellular pathways is unknown. In general, the numbers of mRNAs predicted to be targeted by an miRNA vary greatly from hundreds to thousands, and are dependent on experimental approaches. To comprehensively and accurately identify erythroid miR-144/451 target mRNAs, we compared gene knockout and wild-type fetal liver erythroblasts by RNA sequencing, quantitative proteomics, and RNA immunoprecipitation of Argonaute (Ago), a component of the RNA-induced silencing complex that binds miRNAs complexed to their target mRNAs. Argonaute bound ∼1400 erythroblast mRNAs in a miR-144/451–dependent manner, accounting for one-third of all Ago-bound mRNAs. However, only ∼100 mRNAs were stabilized after miR-144/451 loss. Thus, miR-144 and miR-451 deregulate <10% of mRNAs that they bind, a characteristic that likely applies generally to other miRNAs. Using stringent selection criteria, we identified 53 novel miR-144/451 target mRNAs. One of these, Cox10, facilitates the assembly of mitochondrial electron transport complex IV. Loss of miR-144/451 caused increased Cox10 mRNA and protein, accumulation of complex IV, and increased mitochondrial membrane potential with no change in mitochondrial mass. Thus, miR-144/451 represses mitochondrial respiration during erythropoiesis by inhibiting the production of Cox10.